Evaluasi Strategi Dalam Manajemen Pengendalian Mutu Pembelajaran Program Studi PGMI Fakultas Tarbiyah IAIN Kediri - Dewi Agustriani (JoIEM (Journal of Islamic Education Management), 2023)
Various strategies are carried out by tertiary institutions including study programs in them to improve and control the quality of learning in order to increase the competitiveness of institutions. The purpose of this study is to clarify the evaluation of the strategy carried out by the PGMI Study Program, Faculty of Tarbiyah IAIN Kediri in controlling the quality of learning. The research method used in this study is a qualitative approach to the type of case study design. For the data collection method is done by observation, interviews and documentation. The results of the study show that the design of strategies related to the quality of the study program is written on the Vision and Mission Objectives of the Strategy (VMTS) of the study program. The implementation of this strategy was carried out during lectures taking into account the academic guidelines of the PGMI Study Program. Strategy evaluation is carried out by monitoring and evaluating learning at the beginning, middle and end of the semester. The forms of evaluation activities are study program meetings, Management Review Meetings (RTM), Student Lecturer Evaluations (EDOM) and Internal Quality Audits (AMI). The conclusion from the evaluation of this strategy shows that the quality control of PGMI Study Program learning has been carried out properly. Implementation of learning is in accordance with the curriculum, learning support activities have been carried out according to the planned program and learning facilities have begun to be improved.